The English Prefixes Analysis with Reference to Agricultural Development in a Frontier Region of Java: Besuki, 1870 – Early 1990s - Radnyani, Ni Luh (Humanis, 2018)
Prefix is a bound morpheme which is added to the initial of the base word. This study is concerned with the types, meanings and functions of the English Prefixes found in a scientific book entitled “Agricultural Development in a Frontier Region of Java: Besuki, 1870 – Early 1990s” by Nawiyanto. This study applied two theories in order to analyze the data. The first is the theory of type and meaning of the English prefixes proposed by Quirk (1973). The second is the theory of functions of the English prefixes proposed by Bauer (1983). The data of this study were taken directly from the scientific book itself. The data were collected using the content-analysis method and note-taking technique. The collected data were analyzed using the descriptive and qualitative method. Then, all of the analyses were presented using both formal and informal methods. The analyses show that almost all types of the English prefixes found in the book. However, most of them belong to the class-maintaining English prefixes and the attachment of those prefixes give a new meaning to the base words after its attachment.